2014
DOI: 10.1586/14760584.2014.852961
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic cancer vaccines: a long and winding road to success

Abstract: Harnessing the immune system to achieve therapeutic efficacy in cancer has been a milestone in immuno-oncology. Tumor-induced suppression works as an obstacle for the effectiveness of immunotherapies. Advances in our understanding of the interrelationship between cancer immunoediting and immunotherapy led to successful manipulation of anticancer immunity; this provided the platform for combining cancer vaccines with chemotherapies counteracting, to some extent, tumor-induced suppressive entities and demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 92 publications
(133 reference statements)
0
8
0
Order By: Relevance
“…Many types of vaccine vectors have achieved varying degrees of scrutiny in the tumor immunology field and each have their advantages and disadvantages relating to issues of safety, patient compliance, financial cost, immune potency and labor intensiveness [34, 35]. Delivery of vaccines using attenuated viruses encoding tumor antigen can be a highly efficient way of generating antitumor cellular immune responses, however, such vaccines may be prone to inducing unwanted immune responses or be neutralized by the host’s own antibodies [5, 3639].…”
Section: Introductionmentioning
confidence: 99%
“…Many types of vaccine vectors have achieved varying degrees of scrutiny in the tumor immunology field and each have their advantages and disadvantages relating to issues of safety, patient compliance, financial cost, immune potency and labor intensiveness [34, 35]. Delivery of vaccines using attenuated viruses encoding tumor antigen can be a highly efficient way of generating antitumor cellular immune responses, however, such vaccines may be prone to inducing unwanted immune responses or be neutralized by the host’s own antibodies [5, 3639].…”
Section: Introductionmentioning
confidence: 99%
“…Hoon et al [30] reported a benefit for whole-cell vaccine treatment in HLA-A25-positive patients, as well as a favorable outcome of patients whose HLA expression matched the HLA phenotype expressed by the three melanoma cells lines that composed the vaccine (i.e., HLA-A3/11 and HLA-B7/44). Recombinant tumor antigens including several cancer testis antigens (e.g., MAGE-A3) but also differentiated and overexpressed antigens (HER-2) are presently among the most promising candidate cancer vaccines under evaluation [31][32][33]. However, the HLA class I restriction of total CTL responses induced by these vaccines have not been assessed systematically in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although immunotherapy has emerged as an alternative option for the treatment of cancer patients in the last decades, the presented evidence indicates that both active and adoptive immunotherapeutic strategies are somewhat effective against small tumor burdens, but are generally insufficient to eliminate the disease in patients with advanced stage cancer, despite induction of tumor-specific immune responses [1]. Furthermore, while vaccine approaches have had some clinical achievement, most cancer vaccines fail to induce objective tumor shrinkage in patients.…”
Section: Tumor Microenvironment; Antitumor Immunitymentioning
confidence: 99%
“…In addition to being part of the current treatment armamentarium for metastatic melanoma, immune checkpoint blockade is currently undergoing phase III testing in several cancer types [2]. Targeting co-inhibitory and co-stimulatory receptors with immunostimulatory antibodies has also shown clinical promise and its combined use with vaccines is a promising new approach of immunotherapy for cancer [1].…”
Section: Tumor Microenvironment; Antitumor Immunitymentioning
confidence: 99%
See 1 more Smart Citation